Incidence of suicide, hospital-presenting non-fatal self-harm, and community-occurring non-fatal self-harm in adolescents in England (the iceberg model of self-harm): a retrospective study. (February 2018) - Geulayov, Galit; Casey, Deborah; McDonald, Keltie C; Foster, Pauline; Pritchard, Kirsty; Wells, Claudia; Clements, Caroline; Kapur, Navneet; Ness, Jennifer; Waters, Keith; Hawton, Keith
Summary: Background: Little is known about the relative incidence of fatal and non-fatal self-harm in young people. We estimated the incidence of suicide, hospital-presenting non-fatal self-harm, and community-occurring non-fatal self-harm in adolescents in England. Methods: We used national mortality statistics (Jan 1, 2011, to Dec 31, 2013), hospital monitoring data for five hospitals derived from the Multicentre Study of Self-Harm in England (Jan 1, 2011, to Dec 31, 2013), and data from a schools survey (2015) to estimate the incidence of fatal and non-fatal self-harm per 100 000 person-years in adolescents aged 12–17 years in England. We described these incidences in terms of an iceberg model of self-harm. Findings: During 2011–13, 171 adolescents aged 12–17 years died by suicide in England (119 [70%] male and 133 [78%] aged 15–17 years) and 1320 adolescents presented to the study hospitals following non-fatal self-harm (1028 [78%] female and 977 [74%] aged 15–17 years). In 2015, 322 (6%) of 5506 adolescents surveyed reported self-harm in the past year in the community (250 [78%] female and 164 [51%] aged 15–17 years). In 12–14 year olds, for every boy who died by suicide, 109 attended hospital following self-harm and 3067 reported self-harm in the community, whereas for every girl who died by suicide, 1255 attended hospital for self-harm and 21 995 reported self-harm in the community. In 15–17 year olds, for every male suicide, 120 males presented to hospital with self-harm and 838 self-harmed in the community; whereas for every female suicide, 919 females presented to hospital for self-harm and 6406 self-harmed in the community. Hanging or asphyxiation was the most common method of suicide (125 [73%] of 171), self-poisoning was the main reason for presenting to hospital after self-harm (849 [71%] of 1195), and self-cutting was the main method of self-harm used in the community (286 [89%] of 322). Interpretation: Ratios of fatal to non-fatal rates of self-harm differed between males and females and between adolescents aged 12–14 years and 15–17 years, with a particularly large number of females reporting self-harm in the community. Our findings emphasise the need for well resourced community and hospital-based mental health services for adolescents, with greater investment in school-based prevention. Funding: UK Department of Health.